Soil Seed Banks Are Short-Lived and Triggered by the First Effective Rainfalls in the Vacant Lots of Santiago, Chile - Castro-Morales, S (Elsevier GmbH, 2022)
We studied the temporal variation of the soil seed banks in the urban lots of Santiago, Chile. As most of the plants that emerge from the seed banks in lots are also found in open habitats and are easily germinable, we hypothesize that the seed banks in lots are highly dynamic and short-lived, with the bank depleted every year during the germination season to be reloaded with new seeds during the next seed dispersal period. In each 20 lots for two year (2017 and 2018), 9 soil samples were collected. These samples were obtained from three sampling points randomly distributed across the plots. The seed bank was estimated by seed germination in soil samples placed in plastic trays. The samples of all the lots were stratified at 2 °C by 3 months before sowing. In order to record the seed persistence, soil of three lots watered in 2017 for six months were dried and maintained under dark and non-watered conditions until re-sowing in autumn 2018. To determine if the seeds present cold-associated germination triggers, soils of five lots were maintained under dark conditions for 3 months (soils without cold stratification) for comparison with soils with cold stratification of the same lots. The above-ground plants were recorded in all lots for both years. Forty plant species were recorded in soil bank. The total emerged seedling densities ranged between 7,944 (2017) to 3,700 seedlings m-2 (2018). Species per lot varied between 17 and 7 during 2017, and between 14 and 3 during 2018. In five lots, seedling densities were not statistically different between cold stratified soil at 2 ° C and non-stratified. In three lots with re-sown soil, seedling density of the first sowing (4,096 seedlings m-2) was significantly higher than second sowing (201 seedlings m-2). Thirty-seven plant species were recorded in the above-ground vegetation during 2017 and 42 species in 2018. Species frequency of the seed bank was positively correlated with species frequency of above-ground vegetation. Concluding, the bank is highly dynamic, short-lived, and is depleted every year during the germination season, which begins with effective rainfalls, would be reloaded with seeds during the seed dispersal period. © 2021 Elsevier GmbH